2021
DOI: 10.1037/neu0000760
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mood and cognition on daily functioning and quality of life in older people living with HIV and people with Parkinson’s disease.

Abstract: Objective: In light of the increased longevity of people living with HIV infection (PLWH) undergoing antiretroviral therapy (ART), the present study aimed to determine the effects of mood disturbances alongside cognitive and motor symptoms on activities of daily living (ADLs) and quality of life (QOL) in older PLWH in comparison to an aging control sample without notable medical history (CTL) and individuals with Parkinson's disease (PD). Method: Forty-one PLWH, 41 individuals with PD, and 37 CTL, aged 45-79 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 141 publications
0
1
0
Order By: Relevance
“…We found few studies evaluating cognitive function in PLWH and they are mainly focused on older people [ 54 ] or people with auto degenerative diseases [ 55 ]. Similar to our study, the reported prevalence of cognitive impairment in PLWH varies between 30 and 60% [ 56 , 57 ] and cognitive dysfunction is more prevalent among older adults living with HIV [ 54 , 55 ], which would be expected, given that cognitive impairment is known to increase with aging. Greater age has also been associated with fewer social interactions and a smaller social network [ 57 ], this data is in agreement with our study.…”
Section: Discussionmentioning
confidence: 99%
“…We found few studies evaluating cognitive function in PLWH and they are mainly focused on older people [ 54 ] or people with auto degenerative diseases [ 55 ]. Similar to our study, the reported prevalence of cognitive impairment in PLWH varies between 30 and 60% [ 56 , 57 ] and cognitive dysfunction is more prevalent among older adults living with HIV [ 54 , 55 ], which would be expected, given that cognitive impairment is known to increase with aging. Greater age has also been associated with fewer social interactions and a smaller social network [ 57 ], this data is in agreement with our study.…”
Section: Discussionmentioning
confidence: 99%